Heart-shaped box - Hill, Joe (William Morrow, an imprint of HarperCollinsPublishers, 2023)
"Sooner or later, the dead catch up ... Judas Coyne is a collector of the macabre: a cookbook for cannibals, a used hangman's noose, a snuff film. Many of these objects were gifts from the black-clad fans who made his metal band a legend and made him rich. But not all. When is personal assistant told him there was a ghost for sale on the internet, Jude knew he had to have it for his private collection. He didn't think twice. He should have. Jude has spent a lifetime evading ghosts--his abusive father; the bandmates he betrayed; Anna, the suicidal girl he loved and abandoned. But this spirit is different. This one means to chase him to the edge of sanity. He new acquisition--delivered to his doorstep in a black heart-shaped box--is the restless soul of Anna's vengeful stepdaddy. Craddock McDermott swore he would settle with Jude for ruining his daughter's life. Soon, everywhere Jude turns, Craddock is there: behind the bedroom door; in Jude's restored vintage Mustang; outside his window; on his widescreen TV. Waiting--with a gleaming razor blade on a chain dangling from one bony hand. If ever there was a case of buyer beware, this is it..."--Back cover.